The rise of European liberalism - Laski, Harold Joseph (Aakar Books, 2005)
Beginning with the new worlds of the Renaissance and the Reformation, this book traces the growth of liberal doctrine through the advent of the French Revolution. It shows the relationship of liberalism to the emerging economic system of capitalism, and the impact of this relationship upon science, philosophy, and literature. Laski explains how the same causes which produced the socially active aspect of liberalism also inspired the growth of socialism.